Expression Analysis of Programmed Cell Death Genes in Porcine Parthenogenesis - Jong-Yoon Son; Sang-Hwan Kim; Duk-Won Jung; Chun-Yeol Ryu; Jong-Taek Yoon (The Korean Society of Animal Reproduction and Biotechnology, 2015)
The nature of molecular mechanisms governing embryonic cell block is largely unknown, but recent reports have demonstrated that proper execution of programmed cell death is crucial for this process. The main objective of this study is to determine effects of programmed cell death on porcine oocytes development in vitro after parthenogenesis. Among the blastocysts matured in 3MA, MAP1LC3A and ATG5 RNA gene expression level increased in the order of Cyst < 3MA < RP. However, Casp-3 and TNF-r RNA gene expression level decreased in the order of RP < 3MA < Cyst. Expression of mTOR within the RP-cultured blastocyst was the most highly to the inner cell mass, while 3MA-cultured blastocyst showed very lowest expression in inner cell mass. The expression of mTOR showed a pattern opposite to that of MAP1LC3A. That is, its expression was the lowest in Cyst group. When the enzymatic activity of MMP-2 and MMP-9 was assessed in culture, the level of active MMP-9 was higher expression in the medium of each RP treatment group, with the level of another treatment group being relatively higher. Analyses of TIMP-2 and TIMP-3 revealed that their expression was higher in groups that did not receive RP treatment. More specifically, the level of TIMP-2 was not affected by Cyst treatment, while the level of TIMP-3 was higher in 3MA and RP treatment group. There was highly cell division activation efficiency of parthenogenesis on cultured system of RP supplement IVC medium. Therefore, these results suggest that embryo development was significantly increased in conditional culture medium with active autophagy as compared to common cultured condition. Further investigation of this distinction may enable the development of innovative improvements for the production of porcine somatic cell nuclear transfer.